REPRESENTATION OF THE TRAUMA FROM THE SKOPJE EARTHQUAKE IN 1963 IN THE LAMENT SONGS COLLECTED BY VASIL HADJIMANOV (Philological Studies, 2024)
The paper is based on the recently published laments from the Skopje earthquake in 1963 from the archival materials of Vasil Hadjimanov. Its objective is to show the representation of the trauma from the Skopje earthquake as a significant memory determinant of our collective identity. Hadjimanov's laments demonstrate the presence of trauma in Macedonian folk culture and the implications of the catastrophic earthquake to the folkloric memory of the immediate witnesses of one of the key traumatic events in the history of the city and the country.The paper presents the significant differences of motives in comparison to the previous records of Macedonian laments. It analyzes the representations of the trauma caused by the natural disaster that brought sudden death to a huge number of victims. These laments present numerous details from the biography of the victims talkingabout their life before the traumatic event. At the same time, they represent a description of the social reality as a temporal, spatial and historical setting in which the trauma takes place. By means of reconstruction of the event, the individual suffering is merged into the collective trauma.